A Documentary Note on a Letter to Joseph Smith. Romance, Death, and Polygamy The Life and Times of Susan Hough Conrad and Lorenzo Dow Barnes - Smith, William V. (2016)
The author discusses the life of female Latter-day Saints Lorenzo Dow Barnes and Susan Hough Conrad focusing on letter written to religious leader Joseph Smith by a Mormon missionary Jedediah Morgan Grant. Topics include Joseph Smith's practice of polygamy, Mormon church missions in Antebellum America, and oppositions of the Mormon Church to polygamy.
Keywords: BARNES, Lorenzo Dow; CONRAD, Susan Hough; Mormon Church -- History; Polygamy -- Religious aspects -- Mormon Church; Smith, Joseph, 1805-1844